A Debilitating Orthopaedic Complication following Corticosteroid Therapy for Polymyalgia Rheumatica - Paul Rai; Vinay Takwale (Case Reports in Rheumatology)
Avascular necrosis (AVN) of the scaphoid secondary to corticosteroid use is a rare entity. Previous reports in the literature refer to chronic steroid intake. We report a case secondary to low dose, short term use. AVN has a multifactorial cellular and genetic aetiology and most frequently affects the femoral head. Diagnosis relies on a high index of suspicion and early magnetic resonance (MR) scanning. Treatment options are similar to those of traumatic scaphoid nonunions and include vascularised bone grafting and scaphoid excision. Polymyalgia Rheumatica is a common condition and its treatment is led by corticosteroid use. Mild to moderate strengths are advocated. However in our report we show that even with small doses serious adverse effects can be encountered.